2020
DOI: 10.3390/plants9101259
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Application Boosts Photosynthesis and Sorbitol Biosynthesis and Accelerates Cold Acclimation of Common Plantain (Plantago major L.)

Abstract: Potassium (K) is essential for the processes critical for plant performance, including photosynthesis, carbon assimilation, and response to stress. K also influences translocation of sugars in the phloem and regulates sucrose metabolism. Several plant species synthesize polyols and transport these sugar alcohols from source to sink tissues. Limited knowledge exists about the involvement of K in the above processes in polyol-translocating plants. We, therefore, studied K effects in Plantago major, a species tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 62 publications
3
6
0
Order By: Relevance
“…We found that concentrations of the monosaccharides glucose and fructose increased in the leaf tissue at 0°C (Supplementary Figure S5), in a manner similar to other plant species in which these sugars accumulate during cold treatment (Usadel et al, 2008;Klemens et al, 2014;Ho et al, 2020). The concentrations of glucose and fructose were highest in the leaves, whereas concentrations of sucrose were highest in the heterotrophic storage parenchyma (Supplementary Figure S5).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We found that concentrations of the monosaccharides glucose and fructose increased in the leaf tissue at 0°C (Supplementary Figure S5), in a manner similar to other plant species in which these sugars accumulate during cold treatment (Usadel et al, 2008;Klemens et al, 2014;Ho et al, 2020). The concentrations of glucose and fructose were highest in the leaves, whereas concentrations of sucrose were highest in the heterotrophic storage parenchyma (Supplementary Figure S5).…”
Section: Discussionsupporting
confidence: 70%
“…Sugar alcohols, organic acids, raffinose, and galactinol were quantified via ion-chromatography as described by Ho et al, 2020. Briefly, a 761 Compact IC system (Metrohm, Herisau, Switzerland) was used.…”
Section: Metabolite Extraction and Quantificationmentioning
confidence: 99%
“…Sugar concentrations, especially those of monosaccharides, increased at 0°C in the leaf tissue ( Supplemental Figure S3 ) in a similar manner as in other plant species, where metabolites accumulate during prolonged cold treatment (Ho et al, 2020; Klemens et al, 2014; Usadel et al, 2008). Overall, concentrations of sucrose were highest in the heterotrophic tissues, whereas concentrations of the monosaccharides glucose and fructose were highest in the leaves ( Supplemental Figure S3 ).…”
Section: Discussionsupporting
confidence: 67%
“…Upon exposure to low temperatures, plants increase their overall sugar content in leaves drastically within a comparably short time, usually within one to three days, in a process known as cold acclimation (Klemens et al ., 2013; Rodrigues et al ., 2020; Ho et al ., 2020). In Arabidopsis, cold acclimation-dependent sugar accumulation occurs mainly in vacuoles and depends on TST proteins (Klemens et al, 2013, Vu et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, sugars affect early plant germination, development of the vasculature or govern onset of flowering. It is well known that sugars are key components controlling yield of fruits and storage organs and influence positively plant tolerance to abiotic stresses like drought or cold temperatures (Ruan, 2014;Le Hir et al, 2015;Julius et al, 2017;Pommerrenig et al, 2020;Keller et al, 2021).…”
Section: Discussionmentioning
confidence: 99%